Musical Haptics - Papetti, Stefano; Saitis, Charalampos (Springer Series on Touch and Haptic Systems,, 2018)
This Open Access book offers an original interdisciplinary overview of the role of haptic feedback in musical interaction. Divided into two parts, part I examines the tactile aspects of music performance and perception, discussing how they affect user experience and performance in terms of usability, functionality and perceived quality of musical instruments. Part II presents engineering, computational, and design approaches and guidelines that have been applied to render and exploit haptic feedback in digital musical interfaces. Musical Haptics introduces an emerging field that brings together engineering, human-computer interaction, applied psychology, musical aesthetics, and music performance. The latter, defined as the complex system of sensory-motor interactions between musicians and their instruments, presents a well-defined framework in which to study basic psychophysical, perceptual, and biomechanical aspects of touch, all of which will inform the designof haptic musical interfaces. Tactile and proprioceptive cues enable embodied interaction and inform sophisticated control strategies that allow skilled musicians to achieve high performance and expressivity. The use of haptic feedback in digital musical interfaces is expected to enhance user experience and performance, improve accessibility for disabled persons, and provide an effective means for musical tuition and guidance.